Dominance of Corrective Action in Local Government Crisis Communication: A Quantitative Content Analysis of Surabaya City Government Press Releases Based on Image Repair Theory - Mohammad Insan Romadhan (INJECT (Interdisciplinary Journal of Communication), 2026)
This study examines the distribution of crisis communication strategies in official press releases issued by the Surabaya City Government between August and November 2024 using the framework of Image Repair Theory. A quantitative approach with content analysis was employed to analyze 50 press releases selected through purposive sampling. The unit of analysis was each press release document in its entirety, categorized based on the most dominant crisis communication strategy. Inter-coder reliability measured using Cohen’s Kappa indicated a high level of agreement (κ = 0.82). The findings reveal that Corrective Action is the most dominant strategy (56%), followed by Reducing Offensiveness (30%), Evading Responsibility (12%), and Mortification (2%), while Denial was not identified in the sample. These results suggest that local government crisis communication is primarily action-oriented and focused on issue management rather than rhetorical confrontation or outright rejection. The study contributes to public sector crisis communication research by demonstrating that institutional legitimacy in local governance contexts is largely constructed through administrative action rather than defensive strategies.